Hubungan antara Iklim Komunikasi Suportif dan Motivasi Berorganisasi dengan Komitmen Afektif Anggota Remaja Islam Masjid Agung Jawa Tengah (RISMA JT) - Muhammad Nur Ahadi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2013)
The main aim of this sudy is to determine the relationship between supportive communication climate and organizational motivation with affective commitment of the members of RISMA JT. The population are the members of RISMA JT focused on V, VI, and VII generations amounting to 335 people. The results showed that there is a significant relationship between supportive communication climate and affective commitment (R=0,397 p=0.011). Organizational motivation has a significant relationship with affective commitment (R=0,314 p=0,043). Furthermore, the correlation test results between supportive communication climate and organizational motivation with affective commitment using statistical techniques Kendall-W test showed a probability value of 0.191 (> 0.05) meaning that there’s not simultaneously significant relationship between the three variables. Key Words: Supportive Communication Climate; Organizational Motivation; Affective Commitment